Eu(fod)3 binding on the 1H-NMR spectra of some benzo[3n]crown-n and dibenzo[3n+2]crown-n - Tuncer, H; Erk, Ç (Elsevier Science Bv, 2003)
The complexing of Eu(fod)(3) with macrocyclic, ethers, benzo[15]crown-5, benzo[12]crown-4, dibenzo[20]crown-6, dibenzo[23]crown-7 and dibenzo[26]crown-8 was observed on their H-1-NMR spectra and the selective binding constants at 400 MHz and 305 K in CDCl3 were reported. The Eu(fod)3 interaction displayed the selective binding role of oxygen on macrocyclic, H2C-O-CH2, backbones with o- or m-dioxyphenyl groups referring the H-1 chemical shifts. The estimated equilibrium constants, K-a of 1: 1 ratio of interactions were in accordance with the Eu3+ ionic radii to bind the oxygen sites depending on the macrocyclic size and conformation of the ethers. The minimum lanthanide-macrocyclic ether distance displayed the maximum stability so that benzo[3n]crown-n (n = 4, 5) group was found to bind the Eu(fod)3 moderately whilst dibenzo[3n + 2]crown-n (n = 6-8) oligomer chemical shifts were induced largely since the such Eu3+ complexes are more stable with larger ethyleneoxy groups. (C) 2002 Elsevier Science B.V. All rights reserved.
Keywords: macrocyclic ethers; Eu(fod)(3); magnetic dipolar shifts; ion binding